Geospatial Evaluation/Analysis of Effects of Climate Change Variabilities on Soil-Water-Plant Relationship in South-Eastern Nigeria - , Okechi, K. K.; , Orakwe, L. C.; , Nwachukwu, C. P. (Archives of Current Research International, 2024)
This study evaluates the geospatial and statistical relationships between climate variability and soil water content across microregions in Southeast Nigeria, where cereal and yam crops are extensively cultivated. Climate parameters, including temperature, rainfall, relative humidity, solar radiation, and wind characteristics, were analyzed to assess their impact on soil moisture—a critical factor for crop yield in this region. Descriptive statistics revealed considerable variation in rainfall and humidity across the study area, while maximum temperatures remained consistently high. Correlation analysis indicated that higher temperatures and solar radiation negatively correlate with soil water content, potentially increasing evapotranspiration and reducing available soil moisture essential for crop growth. Regression analysis further identified temperature, relative humidity, and wind direction as significant predictors of soil water content, explaining approximately 24.1% of its variability. ANOVA results showed no statistically significant differences in soil water content across the regions (Enugu, Awka, and Abakaliki), yet the spatial analysis underscored the influence of specific climate factors on soil moisture levels. This interaction is particularly relevant for yam and cereal production, as these crops are sensitive to soil moisture and temperature fluctuations. High temperatures and low humidity can exacerbate soil water deficits, potentially stunting crop growth and affecting yield stability. Unlike previous studies focused primarily on rainfall impacts, this study highlights temperature and radiation as critical influences on soil water dynamics, filling a knowledge gap in climate impact research specific to the Southeast Nigeria context. These findings provide actionable insights for optimizing irrigation and soil management practices, supporting sustainable crop production under changing climatic conditions.